Comparison of intravenous lidocaine and intravenous lidocaine/paracetamol in prevention of postoperative sore throat after laryngeal mask insertion - Arıcan, Şule; Yılmaz, Resul; Hacıbeyoğlu, Gülçin; Bilge, Ayşegül; Yaman, Rabia; Topal, Ahmet; Tuncer, Sema (Journal of Surgery and Medicine, 2020)
Aim: Postoperative sore throat after general anesthesia with laryngeal mask airway is a common and undesirable complication. There are many agents and methods to prevent this complication. However, there is no study comparing intravenous lidocaine and lidocaine-paracetamol combination in the literature. The objective of this study was to compare the effects of systemic lidocaine and systemic lidocaine-paracetamol combination on postoperative sore throat in patients who underwent general anesthesia with laryngeal mask airway. Methods: A total of 80 patients aged over 18 years with ASA I-III who underwent elective inguinal hernia surgery under general anesthesia with laryngeal mask airway were included in this cross-sectional study. Group LidoPara was administered 1 mg kg-1 lidocaine + 10 mg kg-1 paracetamol, and Group Lido, 1 mg kg-1 lidocaine. Resting and swallowing sore throat and hoarseness were evaluated with a 4-point scale at the postoperative 0th, 2nd, 4th, and 24th hours. Results: Demographic data of the patients were similar (P>0.05). There was no statistically significant difference between the two groups in terms of resting and swallowing sore throat at the postoperative 0th, 2nd, 4th, and 24th hours. No hoarseness was found in both groups at the postoperative 4th and 24th hours. Conclusion: Combined paracetamol and lidocaine was found to affect postoperative resting and swallowing sore throat similar to lidocaine alone.